Towards graphical user interface redefinition without source code access: System design and evaluation - Maia, R. (2019)
Nowadays several interactive computing systems (ICSs) still have Graphical User Interfaces (GUIs) that are inadequate in terms of usability and user experience. Numerous improvements were made in the development of better GUIs however, little has been done to improve existing ones. This might be explained by the fact that most ICSs do not provide source code access. In most cases, this means that only persons with source code access can (easily) enhance the respective GUI. This paper presents a tool using computer vision (CV) algorithms to semi-automatically redefine existing GUIs without accessing their source code. The evaluation of a new GUI obtained from the redefinition of an existing GUI using the tool is described. Results show statistically significant improvements in usability (reduction of interaction mistakes), improved task completion success rate and improved user satisfaction.